The Psychosocial Reactions to COVID-19 Pandemic among Individuals in the Arab World - Bakhet, Souad Mousa Ahmed; Alanazi, Rasis Abdullah; Nori, Rehab Abdullahmeed (European Journal of Multidisciplinary Studies, 2021)
This current study aimed at investigating the psycho social reaction to covid19 among individual in the Arab world. In addition, to discover the relationship between these reactions with various variables like age, gender, educational level, occupation and place of origin and place of residence. An open-end questions set by the researchers distributed via the internet. Five hundred and twenty eight (528) respondents answer the questions, 398 females and 130 males. The result showed that the majority of the respondent never or rarely feel negative psychosocial reactions in the entire question except feeling anxious and Suspicions of any person sneeze and this sound logic because the majority of the respondents have no experience of covid19. Thus, they are not under the pressure of suffering from this dangerous and threating disease. The majority of participants from Saudi and Sudan, and other United Emirate country, simply because the researchers from these two countries. Covid19 major concern are physical aspect of the disease, no one can doubt the importance of the psychosocial issues, which are the concern of this study. Other aspect the religious background of the Arabic country especially Sudan and Saudi are conservative and culture restricted communities, thus their psychosocial reaction colored with these background. This study cannot be generalized to the completely Arabic world but it can give an indicator on how individual in the Arabic world think, feel, and react. The study end with conclusion and some recommendations.
Keywords: Covid-19 pandemic, psychosocial reactions, and Arab world